A recent major merger tale for the closest giant elliptical galaxy Centaurus A. Issue 2 (19th August 2020) - Wang, Jianling; Hammer, Francois; Rejkuba, Marina; Crnojević, Denija; Yang, Yanbin
ABSTRACT: We have used hydrodynamical simulations to model the formation of the closest giant elliptical galaxy Centaurus A. We find that a single major merger event with a mass ratio of up to 1.5, and which has happened ∼2 Gyr ago, is able to reproduce many of its properties, including galaxy kinematics, the inner gas disc, stellar halo ages and metallicities, and numerous faint features observed in the halo. The elongated halo shape is mostly made of progenitor residuals deposited by the merger, which also contribute to stellar shells observed in the Centaurus A halo. The current model also reproduces the measured planetary nebula line-of-sight velocity and their velocity dispersion. Models with a small mass ratio and relatively low gas fraction result in a de Vaucouleurs profile distribution, which is consistent with observations and model expectations. A recent merger left imprints in the age distribution that are consistent with the young stellar and globular cluster populations (2–4 Gyr) found within the halo. We conclude that even if not all properties of Centaurus A have been accurately reproduced, a recent major merger has likely occurred to form the Centaurus A galaxy as we observe it at present day.